Woods and forests - Martin, Patricia A. Fink, 1955- (New York : F. Watts, 2000)
Provides instructions for projects and activities that explore forest habitats and demonstrate why they are valuable.
Includes bibliographical references (p. 134-135) and index.
Book Report.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Forest ecology -- Study and teaching -- Activity programs -- Juvenile literature; Ecology -- Experiments; Experiments; Forest ecology -- Experiments; Ecology -- Experiments; Forest ecology -- Experiments; Science -- Experiments